Legal institutions and our moral reasons - Van wees, N (2024)
State institutions, such as courts and legislatures, engage in certain practices. They adopt statutes, decide disputes, and so on. These legal practices often affect our moral world. Can we understand our legal practices just by looking to their moral effects? In this thesis, I argue that we can.